Understanding national e-government: the role of central government. (21st January 2009) - Mofleh, Samer; Wanous, Mohammed; Strachan, Peter
E-government generally refers to the implementation of information and communications technology to change the structures and processes of government organisations aiming at performance improvement. Many governments worldwide invested heavily in national e-government. However, e-government is a recent, multidisciplinary topic that involves various stakeholders. There are different types of e-government and e-government itself is dynamic with an evolving nature. This led to the lack of clear understanding of managerial practices surrounding the role of the central government in its deployment and development. This paper presents a generic framework for explaining e-government focusing on the role of the state throughout its deployment.